IMPLEMENTATION OF CHARACTER EDUCATION THROUGH ICT LEARNING AT ELEMENTARY SCHOOL (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The digital revolution is one of the causes of the changing civilization of society. Changes in society occur in the decline of morality and the many social problems that occur in this nation. Character education is a necessity in an effort to face the challenges of globalization at this time. Character education is a movement of education in schools to strengthen the character of students through harmonization of the heart, taste, thought and sports with the support of public involvement and cooperation between schools, families, and society. Character education is a national movement in creating schools to develop learners to have ethics, responsibility, and caring, by applying and teaching good character through an emphasis on universal values. Character education is a deliberate, proactive, and done effort by schools and governments to instill core values ??in ethics, such as caring, honesty, fairness, responsibility, and respect for others. Schools should be able to develop character education through learning, habituation, extracurricular activities, and working with families and communities. That's why it takes the implementation of character education, one of which can be done when learning ICT in Elementary School. This article is a literature review based article using qualitative approach and descriptive-analysis method, trying to study about how character education in Indonesia. The result of the study shows that the process of internalization of character education in ICT learning can be transformed by doing the culture in the school environment by integrating character education in teaching materials so that habituation, assignment and exemplary become an integral, holistic part which continuously become part studied, understood, and practiced in everyday life.